Nusikaltę kunigai XV–XVI a. Žemaičiuose: nuo vaikžudžio Lauryno iki mušeikos Mažvydo. Bažnyčios teismo bylos kaip Žemaitijos christianizacijos etapo įrodymas | Delinquent Clergy in 15th and 16th-Century Žemaitija … - S.C. Rowell (Acta Historica Universitatis Klaipedensis, 2019)
This article surveys the complex issue of the Christianisation of Žemaitija, seeking to illustrate with the aid of Church court sources (supplications to Rome from the end of the 15th century and appeals to the provincial court of appeal in Gniezno), the foundation of churches and altars which took on extra vigour from 1500 onwards until the chaos and destruction caused by the Reformation movements slowed the process of Catholic parish endowment for some time, as the limited amount of boyar disposable income was diverted elsewhere to Protestant foundations. Despite the admittedly restricted network of parish churches, and it is logical to assume that churches were built where the greater concentration of inhabitants lived, it is worth examining the emergence of Catholic practices (piety) – supplications to Rome, the cult of Corpus Christi, indulgences, the popularity of indulgenced fairs, participation in various levels of Church court activity (in Medininkai, Gniezno and Rome), parish fraternities, prevalence of Christian names, the foundation of churches, chapels and altars (with an associated rise in the level of liturgical sophistication demanded by founders, and an increase in the number of Masses being celebrated, and therefore open to attendance, in parish churches). Indeed, by the turn of the 15th and 16th centuries, when all of these factors can be seen, Catholicism was sufficiently rooted in Žemaitijan society at large that any threat to its development could arise only from internal discontentment (in other words, so-called reform movements) rather than any old (pagan) practices.